'Angelic Spirits of '68': Memories of 60s' Radicalism in Responses to the 2010–11 UK Student Protests. Issue 3 (2nd July 2016) - Dean, Jonathan
Abstract: The winter of 2010–11 saw a significant upsurge of student protest in Britain. This paper analyses the numerous references to 60s' radicalism which circulated in responses to the protests, with a focus on left-wing media. Drawing on performativity theory, the paper traces the highly polarised divisions between affirmations and repudiations of '1968' in responses to the protests. This polarisation, I argue, reflects an absence of a clear-cut collective memory of the British radical 60s. More broadly, the paper sheds light on the hitherto under-explored mechanisms through which memories of '1968' shape the discursive and affective landscape of contemporary radical politics.